2018
DOI: 10.1152/ajpregu.00426.2017
|View full text |Cite
|
Sign up to set email alerts
|

Novel regulator of vasopressin secretion: phoenixin

Abstract: The newly described hypothalamic peptide, phoenixin, is produced in the hypothalamus and adenohypophysis, where it acts to control reproductive hormone secretion. Both phoenixin and its receptor GPR173 are expressed in the hypothalamic supraoptic (SON) and paraventricular (PVN) nuclei, suggesting additional, nonreproductive effects of the peptide to control vasopressin (AVP) or oxytocin (OT) secretion. Hypothalamo-neurohypophysial explants released AVP but not OT in response to phoenixin. Intracerebroventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…To investigate this further, Phoenix Pharmaceuticals devised antibodies to the predicted peptide that were used to identify the endogenous peptide for purification. 3 This work identified two predominant isoforms-N-terminally truncated 14 amino acid form identified in cardiac tissue and a 20 amino acid peptide identified in the brain. It has now been demonstrated that phoenixin is cleaved from the C-terminal of small integral membrane protein 20 (SMIM20), although it is yet to be determined how it is cleaved-either by a prohormone convertase or alternatively by ectodomain shedding.…”
Section: Phoenixin-a Novel Neuropeptidementioning
confidence: 90%
“…To investigate this further, Phoenix Pharmaceuticals devised antibodies to the predicted peptide that were used to identify the endogenous peptide for purification. 3 This work identified two predominant isoforms-N-terminally truncated 14 amino acid form identified in cardiac tissue and a 20 amino acid peptide identified in the brain. It has now been demonstrated that phoenixin is cleaved from the C-terminal of small integral membrane protein 20 (SMIM20), although it is yet to be determined how it is cleaved-either by a prohormone convertase or alternatively by ectodomain shedding.…”
Section: Phoenixin-a Novel Neuropeptidementioning
confidence: 90%
“…Most of the functions of phoenixin including potentiation of gonadotropin-releasing hormone (GnRH)-dependent secretion of LH, augmentation of mRNA (messenger ribonucleic acid) expression in GnRH and kisspeptin neurons, stimulation or suppression of reproductive genes, e.g., C/EBP (CCAAT/enhancer-binding protein) mRNA [ 23 ], delaying the onset of estrus [ 24 ] and the increase of plasma vasopressin levels [ 25 ] were shown to be mediated through the GRP173 (G protein-coupled receptor 173). Conversely, blockade of the receptor using GPR173 siRNA (silencing RNA) abolished these effects [ 23 , 24 , 25 ].…”
Section: Mediation Of Phoenixin’s Effectsmentioning
confidence: 99%
“…Since phoenixin was also detected in the SON [ 11 ], phoenixin-20’s effect on vasopressin and oxytocin expression was examined. Icv injection of phoenixin-20 resulted in an increase of circulating vasopressin levels 20–30 min after injection [ 25 ]. Blockade of the GPR173 using GPR173 siRNA administered into the brain ventricle for two consecutive days completely abolished this effect [ 25 ].…”
Section: Effects Of Phoenixinmentioning
confidence: 99%
See 2 more Smart Citations